Implementation of Early Childhood Education Institution Management Based on the Independent Curriculum at Darul Fallah 2 Kindergarten - Agun, Kristina; Alya, Mega; Yanthy S., Suci Ary; Febryanty, Ria; Rizda A. P., Mecca; Sjamsir, Hasbi; Rozie, Fachrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to describe the implementation of Early Childhood Education (PAUD) management based on the Independent Curriculum at Darul Fallah 2 Kindergarten in Samarinda. This study used a descriptive qualitative approach, with the principal and one class teacher as the subjects. Data were collected through interviews and observations, and supported by case studies. The results indicate that Darul Fallah 2 Kindergarten has implemented effective institution management through four main management functions: planning, organizing, implementing, and evaluating. The principal acts as a strategic leader who directs the course of educational activities, while teachers act as facilitators who focus on child-centered learning. The implementation of the Independent Curriculum at this institution emphasizes center-based learning that allows children the freedom to explore according to their interests and talents. The institution also actively involves parents in the educational process and collaborates with external parties, such as community health centers, to support children's growth and development. Human resource management, infrastructure, and learning activities are aligned with the principles of the Independent Curriculum, which fosters independence, creativity, and religious character in children. Therefore, the implementation of the Independent Curriculum-based management at Darul Fallah 2 Kindergarten has created a meaningful, enjoyable, and holistic learning environment for early childhood.